2011
DOI: 10.1038/modpathol.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular extension is a poor predictor of disease recurrence in surgically treated oropharyngeal squamous cell carcinoma

Abstract: Extracapsular extension in squamous cell carcinoma nodal metastases usually predicts worse outcome. However, there are no standard histologic grading criteria for extracapsular extension, and there have been few studies on oropharyngeal squamous cell carcinoma alone. We studied the extent of extracapsular extension utilizing a novel grading system and correlated grades with outcomes while controlling for p16 status. A cohort of surgically treated oropharyngeal squamous cell carcinoma cases were reviewed and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 34 publications
9
170
4
2
Order By: Relevance
“…To complicate matters, radiographic and pathologic definitions of ENE have been inconsistent, difficult to define, and somewhat subjective [9,12,13]. To address the lack of standardized diagnostic criteria and reporting of pENE, Lewis et al [9] proposed a novel grading system for the assessment of ENE and later simplified this scheme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To complicate matters, radiographic and pathologic definitions of ENE have been inconsistent, difficult to define, and somewhat subjective [9,12,13]. To address the lack of standardized diagnostic criteria and reporting of pENE, Lewis et al [9] proposed a novel grading system for the assessment of ENE and later simplified this scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 43.7, 97.7, 82.6, and 87.3%, respectively [8]. Studies have demonstrated that ENE does not correlate with the size of nodal metastases, and ENE may be present in patients with smaller nodes and low burdens of disease [9]. Now that upfront neck dissections are part of the routine treatment of patients with early oropharyngeal squamous cell carcinoma (OPSCC), we have the opportunity to evaluate the accuracy of preoperative imaging with regards to pENE in this patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Several peculiar pathologic features can be seen. First, neck nodal metastases related to HPV-positive OPSCC are frequently large with pushing borders and expansion of the lymph nodes rather than extensive infiltration of the surrounding tissue [10]. In addition, they are very frequently cystic and/or necrotic [11].…”
Section: Metastatic Squamous Cell Carcinoma Of Unknown Primarymentioning
confidence: 99%
“…In addition, there are no standard pathologic ECS grading criteria at this time [28]. In light of this it is not clear whether surgical pathology or pre-operative imaging should be the gold standard for the detection of ECS, or perhaps an alternative imaging feature such as central nodal necrosis should be used to predict overall survival in place of pathological ECS [26].…”
Section: Extracapsular Spread Of Tumor (Ecs)mentioning
confidence: 99%